THE EFFECT OF TEACHING STYLES AND COORDINATION TO THE LEARNING RESULT OF TABLE TENNIS SKILLS - Fitri Amalia; James Tangkudung; Firmansyah Dlis (Program Pascasarjana Universitas Negeri Jakarta, 2018)
The purpose of this research is to know the difference of influence of teaching style and coordination to the learning result of table tennis skill. The research was conducted on Physical education health and recreation University of education indonesia students. The research method used experiment with 2x3 factorial design, using 60 samples. Based on the results of research and discussion can be concluded that are as follows: 1) There is a difference in the influence of command teaching style with reciprocal teaching style to the learning outcomes of table tennis skills to students as a whole. 2) There is a difference in the influence of the command teaching style with the inclusive teaching style on the learning outcomes of table tennis skills to the students as a whole. 3) There is a difference in the influence of reciprocal teaching style with the teaching style of inclusion to the learning outcomes of table tennis skills to the students as a whole. 4) There is an interaction between the teaching style and the coordination of the learning outcomes of table tennis skills to the students. 5) There is a difference in the influence of command teaching style with the reciprocal teaching style on the learning outcomes of table tennis skills in groups of students who have high coordination. 6) There is a difference in the influence of the command teaching style with the inclusive teaching style on the learning outcomes of table tennis skills in the group of highly coordinated students. 7) There is a difference in the influence of reciprocal teaching styles with inclusive teaching styles on the learning outcomes of table tennis skills in groups of highly coordinated students. 8) There is a difference in the influence of the command teaching style with the reciprocal teaching style on the learning outcomes of table tennis skills in groups of students with low coordination. 9) There is a difference in the influence of the command teaching style with the teaching style of inclusion to the learning outcomes of table tennis skills in the group of students who have low coordination. 10) There is a difference in the influence of reciprocal teaching styles with inclusive teaching styles on the learning outcomes of table tennis skills in groups of students with low coordination. Keywords: Teaching Style, Command, Reciprocal, Inclusion, Coordination